Influence of retromolar canal on the anesthetic block of the inferior alveolar nerve: a clinical randomized study - Fortes, João Henrique Parise (2019)
Objectives: The purpose of this clinical study was to evaluate the influence of (RMC) on the efficacy of inferior alveolar nerve block (IANB) by measuring patients response to pressure and thermal tests before and after the anesthetic procedure. Material and Methods: in patients with RMC diagnosed by cone beam computed tomography IANB was evaluated in a randomized, double-blind and split mouth experimental model. Pulp vitality and mucosal pressure tests were performed before and after IANB of one side of the mandible. After one week, the tests were repeated with inferior alveolar nerve block on the opposite side. The patients response to stimuli was assessed by visual analogue scale (VAS) and Mc Gill (McG) scale. Response variables were the percentage of decrease in patient response to thermal and pressure tests. Data were compared between sides with RMC present and absent with Friedman test. Results: Of 273 CBCTs: 89 (32.7%) men, 184 (67.3%) women, 31 (11.35%) had unilateral CMR, indicating that the prevalence of this study was 11.35%. A statistically significant reduction (VAS and McG) was observed after IANB with present and absent RMC. There was a greater reduction in sensitivity response on the sides without RMC in 5 of 9 patients (VAS) and 6 of 9 (McG), however, there were no statistically significant differences between the side with present and absent RMC (Wilcoxon p> 0.05). Conclusion: The presence of RMC can influence the efficacy of IANB.